GUIDELINES FOR INCREASING THE SOLVENCY OF A CONSTRUCTION COMPANY IN CONDITIONS OF ECONOMIC INSTABILITY AND MARTIAL LAW (USING THE EXAMPLE OF LLC “BC RODNICHOK”) - Корбутяк, Аліна; Терещук, Тетяна (SWorldJournal, 2025)
The theoretical principles of the formation of liquidity and solvency of enterprises and characterizes their significance in the conditions of the war economy of Ukraine are highlighted in the article. Emphasis is placed on key financial indicators that